Hubungan Kadar Asam Urat dengan Fraksi Ejeksi pada Pasien Gagal Jantung Kronik di RSUD Dr. Moewardi - Astri, Pinasty Adi; , Dr. Iin Novita Nurhidayati Mahmuda, M.Sc., Sp.PD (2017)
Heart failure is one of cardiovascular diseases that causes progressive health problems with high rates of mortality and morbidity in both of developed and developing countries. One of poor prognostic marker in chronic heart failure is low on left ventricular ejection fraction. In patients with heart failure, uric acid levels correlates with left ventricular ejection fraction as an indicator of deteriorating cardiac function. The aim of this research is to know the correlation between uric acid levels and ejection fraction on chronic heart failure patient in General Hospital Dr. Moewardi. The research is an observational analytic with cross-sectional study approach. The subjects are chronic heart failure patients in General Hospital Dr. Moewardi. Samples were taken by using purposive sampling technique. Data were obtained from patient's medical records in the period of 2013 to 2016. Data were tested by using pearson test. Fifty-five chronic heart failure patients (33 males and 22 females) were studied. Statistical analysis obtained r = -0,405 or moderate correlation (0,4-0,6) with the correlation negative direction (-) and p = 0,001. The conclusion of this research is there is a correlation between uric acid levels and ejection fraction on chronic heart failure patient in General Hospital Dr. Moewardi. Keywords : uric acid levels, ejection fraction, chronic heart failure